Strands, Powers, and Their Shades of Grey - Murphy, Nancey C. (Journal of European Baptist Studies, 2019)
Reggie Williams’ reflections on the lives of three significant activist- theologians - Harriet Tubman, Martin Luther King Jr, and Dietrich Bonhoeffer - serve as the starting point for a consideration of the anti-racist elements in the ethics of James Wm McClendon Jr. Both Williams and McClendon exemplify a narrative approach to Christian ethics out of recognition of the possibilities and limitations that both our embodied selfhood and our cultural heritages bring to the ethical task. Other voices incorporated here are those of Glen Stassen, John Howard Yoder, and George F. R. Ellis.